Indirect effect of societal engagement on corporate image enhancement and commercial performance: Role of Trust and Customers’ Buying Decision - Gnoufougou, Doman (Archives of Business Research, 2019)
In a global context of ethical awareness, the corporate’s stakeholders (employees, customers, suppliers, local authorities, etc.) seem to adhere to a new approach to the Sustainable Development Goals (SDGs) which takes into account the environmental and social problems. Thus, the objective of this research is to establish a theoretical model in which the customer’s buying decision plays a mediating role in the relations between societal engagement, corporate image enhancement and commercial performance and to examine further the moderating role of trust and Customers’ Buying Decision in the aforementioned relationships. The methodology used is based on an exploratory study of a total sample size of 417 respondents. The structural equation using AMOS.21 and the bootstrap method using SPSS.23 were conducted to test the research hypotheses. The results suggest that societal engagement impacts on corporate image enhancement and corporate commercial performance through customer’s purchasing decision. Similarly, Trust subsequently moderates the indirect relationship between societal engagement, corporate image enhancement and corporate commercial performance through customer’s buying decision. Finally, a discussion of the findings, theoretical and managerial implications, and a future research are provided in this article.